School Principal Management In Improving Teacher Competency Vocational School In Jambi Province - Maisah Maisah; Syarifuddin K; Ahmad Syukri (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to look at the phenomenon of school principal management in improving teachers' pedagogical and professional competence. Principal management includes planning, implementation, supporting and inhibiting factors and evaluation carried out by the principal. This research uses a qualitative phenomenology approach which was carried out at State Vocational High Schools in Jambi Province. Data collection techniques include interviews, observation and documentation. The research was carried out at SMK Negeri 4 Sarolangun, SMK Negeri 4 Jambi City and SMK Negeri 4 Tanjung Jabung Timur. Research subjects included school principals, deputy principals, heads of skills programs, teachers and school staff. Research results: (1) principal planning in the form of teacher needs analysis, in house training, teacher internship program, bringing in guest teachers, upskilling and reskilling programs, (2) implementation includes: learning planning, application of learning methods, classroom management, professional development , collaboration with colleagues, curriculum understanding, use of educational technology, teacher skills development, educational research and measurement and evaluation. (3) The supporting factors are: leadership commitment, teacher empowerment, providing space for teachers to develop initiatives. Meanwhile, the inhibiting factors are budget limitations, resistance to change, unavailability of human resources, teachers' insufficient ICT capabilities and lack of support from related parties. (4) Evaluations carried out by school principals include teacher performance assessments, evaluation discussions with teachers, training and professional development. Based on the research findings, it was concluded that management was carried out directly by the school principal in improving the competency of State Vocational School teachers in Jambi Province. Recommendations were submitted to the Indonesian Ministry of Education and Culture, the Jambi Provincial Education Office and the Industrial and Business World to develop teacher competencies in accordance with industry needs.